Sugarcane abandonment mapping in Rio de Janeiro state Brazil - Castro, Pedro; Yin, He; Teixera Junior, Paulo Domingos; Lacerda, Eduardo; Pedroso, Rui; Lautenbach, Sven; Vicens, Raúl Sánchez (Remote sensing of environment, 2022)
The mapping of sugarcane plantations and their changes is relevant to the economy and the environment, notably due to sugarcane's interface in the biofuel industry through ethanol. The necessary mapping of sugarcane crop changes is especially challenging when plantation occurs under smallholders' land ownership structures used for heterogeneous crop management. We evaluated two approaches to address this challenge with the example of sugarcane abandonment in the Norte Fluminense Region, Northeastern Rio de Janeiro state, Brazil. ...